1976
DOI: 10.1111/j.1365-2230.1976.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and humidity on the growth of Trichophyton mentagrophytes spores on human stratum corneum in vitro

Abstract: Summary Trichophyton mentagrophytes spores were grown on human stratum corneum cultures in vitro and exposed to variations in temperature and humidity in an environmental chamber. The optimal temperature range was found to be 27–33° C but reasonable growth was obtained between 24 and 36°C. The optimal humidity was 97% with a very narrow range of 95–98%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, it is difficult to compare results from these manuscripts with the results of the current study because numerous changes in dermatophyte taxonomy make it difficult to determine if the same species are being considered 18 . One study defined the optimal growth temperature for T. mentagrophytes as 27–33°C, 19 which is considerably higher than the temperature range of 20.6–25.6°C observed in the current work. Incubation of plates in the XLIGHT condition brought the cultures closer to the optimal target range, consistent with the observed XLIGHT growth‐stimulatory effect.…”
Section: Discussionmentioning
confidence: 75%
“…However, it is difficult to compare results from these manuscripts with the results of the current study because numerous changes in dermatophyte taxonomy make it difficult to determine if the same species are being considered 18 . One study defined the optimal growth temperature for T. mentagrophytes as 27–33°C, 19 which is considerably higher than the temperature range of 20.6–25.6°C observed in the current work. Incubation of plates in the XLIGHT condition brought the cultures closer to the optimal target range, consistent with the observed XLIGHT growth‐stimulatory effect.…”
Section: Discussionmentioning
confidence: 75%
“…Storing conidia at 100% humidity killed the samples after only 9 days at 22 o C 8 . Other works indicated that Trichophyton mentagrophytes, the other main dermatophytes related to onychomycosis, has a very narrow humidity range of 95-98% and that different levels of humidity are better or worse for different stages of T. mentagrophytes-high humidity is necessary for arthrospore formation but reduced humidity necessary for maturation 19 . While T. mentagrophytes and T. rubrum are not the same, they are similar enough to warrant further studies investigating the effect of humidity and spore creation and growth 6,19,20 .…”
Section: Vacuummentioning
confidence: 99%